2012
DOI: 10.1037/a0024851
|View full text |Cite
|
Sign up to set email alerts
|

Aging and retrospective revaluation of causal learning.

Abstract: In a two-stage causal learning task, young and older participants first learned which foods presented in compound were followed by an allergic reaction (e.g., STEAK - BEANS → REACTION) and then the causal efficacy of one food from these compounds was revalued (e.g., BEANS → NO REACTION). In Experiment 1, unrelated food pairs were used and although there were no age differences in compound or single cue – outcome learning, older adults did not retrospectively revalue the causal efficacy of the absent target cue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Levels of cue competition are associated with the development of reasoning abilities and working memory ( Simms et al, 2012 ; McCormack et al, 2013 ; also see Livesey et al, 2013 ). Mutter et al (2012) observed decreased levels of cue competition in older adults, associated with deterioration in associative memory formation and retrieval. Future developmental research can be expanded to other processes described in the framework.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Levels of cue competition are associated with the development of reasoning abilities and working memory ( Simms et al, 2012 ; McCormack et al, 2013 ; also see Livesey et al, 2013 ). Mutter et al (2012) observed decreased levels of cue competition in older adults, associated with deterioration in associative memory formation and retrieval. Future developmental research can be expanded to other processes described in the framework.…”
Section: Discussionmentioning
confidence: 83%
“…Several of the abovementioned functions (e.g., working memory and inferential reasoning) develop during childhood ( Greenberg et al, 1977 ; Byrnes and Overton, 1986 , 1988 ; Cowan, 1997 ). In late adulthood functions like working memory, associative memory formation and memory retrieval deteriorate ( Hartman et al, 2001 ; Mutter et al, 2006 , 2012 ; Old and Naveh-Benjamin, 2008 ). Research has shown that cue competition emerges alongside the development of these functions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high demand to make decisions under ambiguity, this ability deteriorates disproportionately with age and may correspond to deficits in cue‐cue associations (Mutter et al, ) in humans. Also consistent with the human condition, we found expression of the immediate early gene cFos was correlated between dentate gyrus (DG) and CA1 for rats demonstrating behavioral sensitivity to the ambiguous test, similar to CA1 activity found when humans make an inference (Schlichting et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that young adults readily learn to shift attention to the most relevant stimuli to reduce errors during associative learning (e.g., Kruschke et al, 2005;Le Pelley, Beesley, & Griffiths, 2011). Older adults are less efficient at acquiring cue-outcome associations than young adults (Mutter et al, 2006(Mutter et al, , 2009(Mutter et al, , 2012Mutter & Williams, 2004), but there have been few studies exploring whether this might be due to age-related differences in attention. The goal of this research was to determine whether older adults differ from young adults in their ability to modulate attention to relevant and irrelevant stimuli during associative learning.…”
mentioning
confidence: 99%
“…In this study, we investigated whether age-related deficits in cue–outcome associative learning (e.g., Mutter, Atchley, & Plumlee, 2012; Mutter, DeCaro, & Plumlee, 2009; Mutter, Haggbloom, Plumlee, & Schirmer, 2006; Mutter & Williams, 2004) might be due to a decline in older adults’ ability to modulate attention to relevant and irrelevant cues. In the first 2 experiments, we used standard blocking and highlighting tasks to indirectly measure the ability to shift attention away from irrelevant stimuli toward relevant, predictive cues (e.g., Kruschke, Kappenman, & Hetrick, 2005).…”
mentioning
confidence: 99%